A multi-period settlement next to the River Spey, Craggan, Grantown-on-Spey (Scottish Historical and Archaeological Internet Reports, 2025)
Archaeological works undertaken in 2019 and 2020 in advance of development of the Cairn Distillery, Grantown-on-Spey identified remains of a multi-period landscape spanning the Late Mesolithic to the medieval period. The earliest phase of activity on site was evidenced by residual material from the Mesolithic-Neolithic transition. A Late Neolithic cremation pit was also identified, comprising the cremated remains of at least one adult male. Following this funerary activity, the remains of a Late Bronze Age fire pit were identified. Additionally, at least three post-defined Middle Iron Age roundhouses and metalworking features were recorded. Late Iron Age and early medieval settlement and industrial activity was evidenced by the remains of at least three roundhouses, with fire and refuse pits, a four-post granary, a metalworking furnace, and metal waste pits. The artefact assemblage included worked and coarse stone, as well as metal finds. Notable stone finds included a Late Mesolithic chipped stone, several Late Iron Age rotary quernstones and a large millstone roughout, while Middle Iron Age and early medieval slag and metalworking waste were indicative of small-scale smelting at the site. The finds at Craggan represent a significant site along the River Spey, comprising multiple phases of settlement, funerary activity, and craftworking from the Mesolithic to the medieval period.